Redescription of the eel Ilyophis arx Robins, 1976 (Anguilliformes: Synaphobranchidae: Ilyophinae) with a description of a new species of Ilyophis, and a taxonomic synopsis of the Ilyophinae - Tighe, Kenneth A.; Smith, David G.; Merrett, Nigel R.; Frable, Benjamin W.; Zajonz, Uwe (Zootaxa, 2024)
Ilyophis arx Robins, 1976 is redescribed based on the four type specimens from south of the Galapagos Islands and 21 additional specimens: 12 specimens from the western Clarion Clipperton Zone in the central Pacific Ocean, four specimens from the eastern Pacific Ocean, and five specimens from several localities in the central North Pacific Ocean. A new species, Ilyophis maclainei sp. nov., is described from the eastern North Atlantic. A taxonomic synopsis of the subfamily Ilyophinae is presented, and a key to the known species is provided.